Critical Temperature-Humidity Index Thresholds for Dry Cows in a Subtropical Climate - Ouellet, Véronique; Toledo, Izabella M.; Dado-Senn, Bethany; Dahl, Geoffrey E.; Laporta, Jimena (Frontiers in Animal Science, 2021)
The effects of heat stress on dry cows are profound and significantly contribute to lower overall welfare, productivity, and profitability of the dairy sector. Although dry cows are more thermotolerant than lactating cows due to their non-lactating state, similar environmental thresholds are currently used to estimate the degree of heat strain and cooling requirements. Records of dry cow studies conducted over 5 years in Gainesville, Florida, USA were pooled and analyzed to determine environmental thresholds at which dry cows exhibit signs of heat stress in a subtropical climate. Dry-pregnant multiparous dams were actively cooled (CL; shade of a freestall barn, fans and water soakers, n = 107) or not (HT; shade only, n = 111) during the last 7 weeks of gestation, concurrent with the entire dry period. Heat stress environmental indices, including ambient temperature, relative humidity, and temperature-humidity index (THI), and animal-based indices, including respiration rate, rectal temperature and daily dry matter intake were recorded in all studies. Simple correlations were performed between temperature-humidity index and each animal-based indicator. Differences in respiration rate, rectal temperature and dry matter intake between treatments were analyzed by multiple regression. Using segmented regression, temperature-humidity thresholds for significant changes in animal-based indicators of heat stress were estimated. Stronger significant correlations were found between the temperature-humidity index and all animal-based indices measured in HT dry cows (−0.22 ≤ r ≤ 0.35) relative to CL dry cows (−0.13 ≤ r ≤ 0.19). Although exposed to similar temperature-humidity index, rectal temperature (+0.3°C; P < 0.001) and respiration rate (+23 breaths/min; P < 0.001) were elevated in HT dry cows compared with CL cows whereas dry matter intake (−0.4 kg of dry matter/d; P = 0.003) was reduced. Temperature-humidity index thresholds at which respiration rate and rectal temperature began to change were both determined at a THI of 77 in HT dry cows. No significant temperature-humidity threshold was detected for dry matter intake. At a practical level, our results demonstrate that dry cow respiration rate and rectal temperature increased abruptly at a THI of 77 when provided only shade and managed in a subtropical climate. Therefore, in the absence of active cooling, dry cows should be closely monitored when or before THI reaches 77 to avoid further heat-stress related impairments during the dry period and the subsequent lactation and to mitigate potential carry-over effects on the offspring.